2017
DOI: 10.1042/bsr20160576
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-130a-3p inhibits the viability, proliferation, invasion, and cell cycle, and promotes apoptosis of nasopharyngeal carcinoma cells by suppressing BACH2 expression

Abstract: The aim of the present study was to explore the mechanism through which miR-130a-3p affects the viability, proliferation, migration, and invasion of nasopharyngeal carcinoma (NPC). Tissue samples were collected from the hospital department. NPC cell lines were purchased to conduct the in vitro and in vivo assays. A series of biological assays including MTT, Transwell, and wound healing assays were conducted to investigate the effects of miR-130a-3p and BACH2 on NPC cells. MiR-130a-3p was down-regulated in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
(53 reference statements)
2
26
0
Order By: Relevance
“…Abnormal expression of RPN2 has been reported in breast cancer, non-small cell lung cancer, gastric cancer, colorectal cancer, and prostatic carcinoma. 11 13 In the present study, we observed a marked increase in RPN2 expression in NPC tissues. The subsequent experiments were designed to explore the effect of siRNA-RPN2 treatment on tumor migration and invasion in NPC.…”
Section: Discussionsupporting
confidence: 66%
“…Abnormal expression of RPN2 has been reported in breast cancer, non-small cell lung cancer, gastric cancer, colorectal cancer, and prostatic carcinoma. 11 13 In the present study, we observed a marked increase in RPN2 expression in NPC tissues. The subsequent experiments were designed to explore the effect of siRNA-RPN2 treatment on tumor migration and invasion in NPC.…”
Section: Discussionsupporting
confidence: 66%
“…The downregulation of BACH2 significantly inhibits the viability, migration and invasive ability of glioma cells and promotes glioma cell apoptosis, suggesting that BACH2 may act as an oncogene. Chen et al [32] found that BACH2 is upregulated in NPC, while its knockdown inhibits the proliferation, migration and invasion of NPC cells. BACH2 expression varies in different tumours; CD19+ B cells from mantle cell lymphoma patient samples showed reduced BACH2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐199b‐5p promotes cell aggregation, suppresses cell invasion and migration and inhibits TGF‐β‐induced EMT in hepatocellular carcinoma by inhibiting N‐cadherin . In several studies, miR‐130a‐3p was shown to decrease in cancer tissues and inhibit cell invasion, migration, and EMT . By contrast, miR‐130a‐3p is upregulated in some GC cases and promotes cell proliferation and migration in GC cells.…”
Section: Discussionmentioning
confidence: 99%